MANAGEMENT OF THE TAX SYSTEM IN THE BUKHARA EMIRATE (World Bulletin of Social Sciences, 2025)
In the Emirate of Bukhara, not only certain categories of civil servants but also almost all officials of the Emirate participated in the management of the tax system. Although the names and actual positions of officials and officials in the Emirate were focused on other areas, they also had direct and indirect responsibilities for the management of the tax system. In addition to their main responsibilities, they also carried out the tasks assigned to them in the tax system. The results of the study show that due to the importance of the tax system, which is the main source of state revenue in the Emirate of Bukhara, all officials from the Emir to the local government were responsible for the management and control of the tax system